Pengaruh bahan ajar IPA terpadu bermuatan keterampilan literasi tema gerak dalam kehidupan sehari-hari terhadap kompetensi siswa kelas VIII SMPN 8 Padang - Riski Yuliana; Asrizal Asrizal (Universitas Negeri Padang, 2019)
The 21st century education should be able to develop the literacy of students. In addition, the 2013 curriculum also requires science teaching to be conducted in an integrated patter so that students can learn actively, holistically, meaningfully, and authentically. But the real condition showed that the science teachers experience some difficulties in integrating among the branches of science, namely Physics, Biology, and Chemistry. The integration of learning material in science textbooks was still relatively low and the integration of literacy in science teaching only reading literacy. The solution to this problem is the application of integrated science learning materials by integrating the literacy skills. The purpose of this research was to investigate the effect of integrated science learning material by integrating literacy skills on the theme of motion in everyday life towards the competencies of grade VIII students in SMPN 8 Padang. The type of research was a quasi-experimental with randomized posttest-only control group design. The sampling technique used both purposive sampling and cluster random sampling. The instruments for collecting data were observation attitude sheets for attitude competencies, written test sheets for knowledge competencies, and performance sheets for skills competencies. The data of the research were analyzed by using the descriptive statistical analysis and two means comparison test. Based on data analysis, it can be stated that integrated science learning material by integrating the literacy skills on the theme of motion in everyday life has a significant effect on the competency of grade VIII students including aspects of attitudes, knowledge, and skills at the 95% confidence level. This result indicates that the use of integrated science learning material by integrating literacy skills on the theme of motion in everyday life is effective to be applied in a scientific approach.